2020
DOI: 10.1021/acs.iecr.9b05712
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Quartz Sand and Wood Doped with either K or Na Salts under Steam Gasification and Combustion Atmospheres

Abstract: The interactions between quartz sand and wood, which was doped with either K or Na salts, were investigated in a lab-scale, fixed-bed reactor under either a steam gasification or a combustion atmosphere at 900 °C. For the cases of the potassium/sodium phosphate salts, the interaction was found to be melting induced, while for the cases of the other salts, it was found to be coating induced. Large agglomerates were found to have already been formed during the early stages of steam gasification for the wood samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(42 citation statements)
references
References 45 publications
4
38
0
Order By: Relevance
“…Therefore, the K components from grape marc were mostly retained in the solid agglomerates, which implies that the retention ratio of K in the silica bed is closely associated with agglomeration processes. It has been previously suggested that the presence of steam facilitates hydrolysis of K salts, which was found to favor the reaction with silica sand and therefore retained more K in the agglomerates under a steam gasification atmosphere compared with that of the combustion atmosphere . In contrast, for the cases with olivine as the bed material, K was found to retain in the bed in the solid ash particles other than reacting with the bed material under the combustion or the steam gasification atmosphere.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, the K components from grape marc were mostly retained in the solid agglomerates, which implies that the retention ratio of K in the silica bed is closely associated with agglomeration processes. It has been previously suggested that the presence of steam facilitates hydrolysis of K salts, which was found to favor the reaction with silica sand and therefore retained more K in the agglomerates under a steam gasification atmosphere compared with that of the combustion atmosphere . In contrast, for the cases with olivine as the bed material, K was found to retain in the bed in the solid ash particles other than reacting with the bed material under the combustion or the steam gasification atmosphere.…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously suggested that the presence of steam facilitates hydrolysis of K salts, 71−73 which was found to favor the reaction with silica sand and therefore retained more K in the agglomerates under a steam gasification atmosphere compared with that of the combustion atmosphere. 9 In contrast, for the cases with olivine as the bed material, K was found to retain in the bed in the solid ash particles other than reacting with the bed material under the combustion or the steam gasification atmosphere. In this context, the retention of K in the olivine bed under the two atmospheres would then be solely reliant on the ash transformation characteristics of grape marc.…”
Section: K Retention During Interactionmentioning
confidence: 89%
See 3 more Smart Citations